2019
DOI: 10.1002/cncr.32130
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor efficacy of arsenic/interferon in preclinical models of chronic myeloid leukemia resistant to tyrosine kinase inhibitors

Abstract: Background Tyrosine kinase inhibitors (TKIs) are the standard treatment for chronic myeloid leukemia (CML). Despite their clinical success, TKIs are faced with challenges such as treatment resistance, which may be driven by kinase domain mutations, and frequent disease relapse upon the cessation of treatment. The combination of arsenic trioxide (ATO) and interferon‐α (IFN) was previously demonstrated to inhibit proliferation and induce apoptosis in CML cell lines, prolong the survival of primary wild‐type CML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…Resistance to TKI in CML can lead to disease progression and relapse, especially in advanced stage (El Eit et al, 2019;Sundaram et al, 2019). The mechanism can be broadly classified as either Bcr-Abl-dependent or independent according to if the kinase domain was mutant or not (Ma et al, 2014;Mitchell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to TKI in CML can lead to disease progression and relapse, especially in advanced stage (El Eit et al, 2019;Sundaram et al, 2019). The mechanism can be broadly classified as either Bcr-Abl-dependent or independent according to if the kinase domain was mutant or not (Ma et al, 2014;Mitchell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This complies with the results of the study by Chen et al on discontinuation of first- and second-generation TKIs [ 34 ]. El Eit et al's experimental studies on CML mouse models concluded that IFN may allow TML-resistant CML mice to overcome various TKI-specific resistance mechanisms and achieve durable remission [ 35 ]. This is probably because the dormant state may be the vital mechanism observed for normal HSCs and leukemia stem cells (LSCs) to resist proliferative chemical resistance [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the principal mechanism underlying this success was biphasic—with immune activation induced by dasatinib pre-treatment followed by restoration of immunological surveillance after application of IFN-α therapy [ 91 ]. In vitro, IFN-α combined with arsenic trioxide, synergized to inhibit proliferation and induce apoptosis of imatinib-resistant CML cell lines, whilst in vivo murine models showed significantly prolonged survival of primary T315I-CML mice whilst dramatically impairing disease engraftment in secondary mice [ 92 ]. IFN-α may thus provide an alternative therapeutic approach in selected TKI-resistant mutation positive CML patients, particularly those ineligible for alternative options such as BM transplantation.…”
Section: Immunotherapy In Tki-resistant Mutations and Blast-phase Patientsmentioning
confidence: 99%